Pengaruh Strategi Pembelajaran Dan Motivasi Terhadap Kemampuan Gerak Dasar Object Control Siswa Sekolah Dasar - Junaidi, Tri Putra; Bakhtiar, Syahrial; Syafruddin, Syafruddin (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2024)
This research comes from Physical Education lessons in elementary schools, it is clear that children's movements are not good. Even though these basic movement skills are very important for children, especially elementary school age children. in the learning process which aims to reveal the influence of learning strategies and motivation on elementary school students' learning of basic Object Control movements. This type of research is a quasi-experiment. The sample for this research consisted of 20 Class V students at SD 22 Ujung Gurun Kec. Padang Barat Kota Padang uses Total Sampling. The results of this research show that: (1) Basic Object Control Movement Skills given with Exploration style results are higher than Command style (Qh = 5.01 > Qt = 2.983), (2) There is an interaction between learning strategies and achievement motivation on ability children's basic Object Control movements (Fh = 11.77 > Ft = 4.08), (3) With high achievement motivation, the basic Object Control movement abilities of children in the group given the Exploration style were higher than those given the command style (Qh = 5.44 > Qt = 3.216), (4) In low achievement motivation, the basic motor skills of Object Control group children who were given the Exploration style were lower than the Command style (Qh = 56.44 > Qt = 3.216).